TRANQUIL WAVES OF TEACHING, LEARNING AND MANAGEMENT - Johnson-Perkins, James (PEOPLE: International Journal of Social Sciences, 2020)
Exploring aspects of: Teaching, Learning and Management at one of the leading Sino-Foreign Universities, The University of Nottingham, Ningbo, which relate to an Art and Design Tutor, and Academic Lead for History and Social Sciences within The Centre for English Language Education (CELE) Department, from 2014-20. This paper looks at aspects of: Design and planning of learning activities, teaching support of learners, assessment and feedback, the development of effective learning environments (and approaches to student support and guidance) and also at continuing professional development relating to research and scholarship. It also reveals aspects of two case studies pertaining to leadership and coaching.